Increased circulating uric acid aggravates heart failure via impaired fatty acid metabolism - Lou, Bowen; Wu, Haoyu; Ott, Hannes; Bennewitz, Katrin; Wang, Chen; Poschet, Gernot; Liu, Hui; Yuan, Zuyi; Kroll, Jens; She, Jianqing (Journal of translational medicine, 2023)
Increased circulating uric acid (UA) concentration may disrupt cardiac function in heart failure patients, but the specific mechanism remains unclear. Here, we postulate that hyperuremia induces sterol regulatory element binding protein 1 (SREBP1), which in turn activate hepatic fatty acid biosynthesis response, leading to cardiac dysfunction.